2000
DOI: 10.1001/jama.283.22.2961
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Risk of Stroke in Women

Abstract: These data indicate that physical activity, including moderate-intensity exercise such as walking, is associated with substantial reduction in risk of total and ischemic stroke in a dose-response manner. JAMA. 2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
252
2
14

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 444 publications
(273 citation statements)
references
References 40 publications
5
252
2
14
Order By: Relevance
“…These data on physical activity have been assessed using an instrument that was validated in the current population and shown to classify women reasonably well. Using the same activity assessment in parallel studies among slightly older women we have shown that greater activity predicts reduced risk of diabetes , heart disease , stroke (Hu et al, 2000), colon cancer (Martinez et al, 1999), osteoporotic fractures (Feskanich et al, 2002), and reduced weight gain after smoking cessation (Kawachi et al, 1996). In the NHS II, higher physical activity predicts reduced ovulatory infertility (RichEdwards et al, 2002), and is strongly related to lower BMI.…”
Section: Discussionmentioning
confidence: 99%
“…These data on physical activity have been assessed using an instrument that was validated in the current population and shown to classify women reasonably well. Using the same activity assessment in parallel studies among slightly older women we have shown that greater activity predicts reduced risk of diabetes , heart disease , stroke (Hu et al, 2000), colon cancer (Martinez et al, 1999), osteoporotic fractures (Feskanich et al, 2002), and reduced weight gain after smoking cessation (Kawachi et al, 1996). In the NHS II, higher physical activity predicts reduced ovulatory infertility (RichEdwards et al, 2002), and is strongly related to lower BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate-intensity activities such as brisk walking generate 40-60% of maximum oxygen uptake [9,10] and have been associated with reduced risk of coronary heart disease [11], stroke [12,13], and insulin resistance [14]. These beneficial effects are associated with decreases in body weight, blood pressure (BP), serum cholesterol, and improved glucose tolerance [15].…”
Section: Introductionmentioning
confidence: 99%
“…Only 25% of Americans meet the recommended levels of physical activity participation [2] despite the health benefits of a physically active lifestyle (e.g., reduced risk of cardiovascular disease and non-insulin-dependent diabetes) [3,4].…”
Section: Introductionmentioning
confidence: 99%